2011
DOI: 10.1007/s10531-011-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat edge context and the distribution of phyllostomid bats in the Andean forest and anthropogenic matrix in the Central Andes of Colombia

Abstract: Bats play an important role in the ecosystem as seed dispersers, pollinators and pest controllers. In particular, frugivorous bats are important for regeneration processes in open and degraded areas, because they disperse the seeds of pioneer plant species, which are essential for succession. Depending on the type of habitat that is established at the fragment edge, resources and bat movement patterns toward open areas can be affected. The structure and composition of bats was compared between two 'interior-ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Nonetheless, V. caraccioli (Stenodermatinae) was caught exclusively in undisturbed forest, and C. perspicillata (Carolliinae) was caught mainly in riparian pasture habitat, supporting the idea that sedentary bats seldom leave mature forests (Soriano ). In this context, open pastures generate impermeability, because they seem to limit the movement of frugivorous bats restraining seed‐flux between fragments and their matrix process that is crucial in the recovery in old fields (Cortés‐Delgado and Pérez‐Torres ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, V. caraccioli (Stenodermatinae) was caught exclusively in undisturbed forest, and C. perspicillata (Carolliinae) was caught mainly in riparian pasture habitat, supporting the idea that sedentary bats seldom leave mature forests (Soriano ). In this context, open pastures generate impermeability, because they seem to limit the movement of frugivorous bats restraining seed‐flux between fragments and their matrix process that is crucial in the recovery in old fields (Cortés‐Delgado and Pérez‐Torres ).…”
Section: Discussionmentioning
confidence: 99%
“…In insular systems, strong evidence indicates that tropical bats displaying low tolerance to edge effect are predisposed to population declines because of habitat fragmentation [17]. However, the magnitude of edge effect depends on the degree of contrast between matrix and patches; a greater effect is observed in high contrast landscapes [11,12], and possibly is less severe in fragmented terrestrial landscapes [7,[61][62][63] because the contrast between border and matrix is less pronounced [63]. Additionally, bats are able to use elements of fragmented landscapes such as corridors, steppingstones, and even the vegetation matrix [3,56,64].…”
Section: Discussionmentioning
confidence: 99%
“…Roosting habits of C. castanea are also dependent on forest; this species is not known to roost in man-made structures or agriculture, but rather appears to roost exclusively in cavities among tree roots in riparian zones (Bonaccorso et al, 2006;Thies, Kalko, & Schnitzler, 2006). Previous studies have found that C. castanea abundance is lower in modified agricultural areas than in interior forest (Cort es-Delgado & P erez-Torres, 2011;Medina, Harvey, Merlo, Vilchez, & Hernandez, 2007), and is especially low in intensive agriculture like full-sun coffee and oil palm plantations (Freudmann et al, 2015;Numa, Verd u, & S anchez-Palomino, 2005).…”
Section: Population Genetic Structure In An Intensifying Agriculturmentioning
confidence: 99%